Wikipedia and osteosarcoma: a trustworthy patients' information? - Leithner, Andreas (BMJ Group, 2010)
The English version of the online encyclopedia, Wikipedia, has been recently reported to be the prominent source of online health information. However, there is little information concerning the quality of information found in Wikipedia. Therefore, we created a questionnaire asking for scope, completeness, and accuracy of information found on osteosarcoma. Three independent observers tested the English version of Wikipedia, as well as the patient version and the health professional version of the US National Cancer Institute (NCI) website. Answers were verified with authoritative resources and international guidelines. The results of our study demonstrate that the quality of osteosarcoma-related information found in the English Wikipedia is good but inferior to the patient information provided by the NCI. Therefore, non-peer-reviewed commonly used websites offering health information, such as Wikipedia, should include links to more definitive sources, such as those maintained by the NCI and professional international organizations on healthcare treatments. Furthermore, frequent checks should make sure such external links are to the highest quality and to the best-maintained aggregate sites on a given healthcare topic.